Dynamic Mode Decomposition of merging wind turbine wakes - Zormpa, M; Le Clainche, S; Ferrer, E; Vogel, CR; Willden, RHJ (IOP Publishing, 2023)
The design and operation of wind farms is significantly affected by the impact that upstream turbine wakes have on the power production and fatigue loading of subsequent turbines; often called the wake effect. In this work, two types of flows are considered: the wake of a single turbine with a laminar inflow and the combined wake of two turbines operating in-line where the upstream wake results in an unsteady inflow for the downstream turbine. Those two scenarios are simulated using large eddy simulation (LES) and the actuator line method (ALM). The spatio-temporal velocity fields are analyzed by means of high order dynamic mode decomposition (HODMD), a well established variant of the DMD. The results show that most of the higher frequencies characterizing the laminar case are instead dominated by the lower frequency modes in the combined wake. This suggests that structures emerging from the blade rotations in a wind turbine wake may be less significant for describing the wake dynamics when the rotor is operating in the unsteady wake of an upstream rotor.